The Boy Who Owned the School : Tales to Tickle the Funnybone #1 - Paulsen, Gary (New York : Orchard Books, 1990)
Jacob Freisten, often in a fog, tries to ease through high school unnoticed; but a beautiful classmate takes notice of him and his life begins to change.
Keywords: High schools -- Fiction